Study Finds Member Support For Quarterly Policy Changes - Clifford W. Scherer (Journal of Applied Communications, 1988)
The study of ACE members conducted in the spring of 1988 provides overwhelming support for the proposed changes in the Quarterly. Sixty-seven percent of ACE members say that they expect ACE to provide a quality publication, but only 42% of all members believe that the Quarterly is a "quality" publication. This finding, perhaps more than any other, supports the proposal for major changes in the Quarterly publishing policy.